PDT-induced epigenetic changes in the mouse cerebral cortex: A protein microarray study - Demyanenko, S.V.; Uzdensky, A.B.; Sharifulina, S.A.; Lapteva, T.O.; Polyakova, L.P. (Biochimica et biophysica acta, 2014)
Photodynamic therapy (PDT) is used for cancer treatment including brain tumors. But the role of epigenetic processes in photodynamic injury of normal brain tissue is unknown. 5-Aminolevulinic acid (ALA), a precursor of protoporphyrin IX (PpIX), was used to photosensitize mouse cerebral cortex. PpIX accumulation in cortical tissue was measured spectrofluorometrically. Hematoxylin/eosin, gallocyanin–chromalum and immunohistochemical staining were used to study morphological changes in PDT-treated cerebral cortex. Proteomic antibody microarrays were used to evaluate expression of 112 proteins involved in epigenetic regulation. ALA administration induced 2.5-fold increase in the PpIX accumulation in the mouse brain cortex compared to untreated mice. Histological study demonstrated PDT-induced injury of some neurons and cortical vessels. ALA-PDT induced dimethylation of histone H3, upregulation of histone deacetylases HDAC-1 and HDAC-11, and DNA methylation-dependent protein Kaiso that suppressed transcriptional activity. Upregulation of HDAC-1 and H3K9me2 was confirmed immunohistochemically. Down-regulation of transcription factor FOXC2, PABP, and hBrm/hsnf2a negatively regulated transcription. Overexpression of phosphorylated histone H2AX indicated activation of DNA repair, but down-regulation of MTA1/MTA1L1 and PML — impairment of DNA repair. Overexpression of arginine methyltransferase PRMT5 correlated with up-regulation of transcription factor E2F4 and importin α5/7. ALA-PDT injures and kills some but not all neurons and caused limited microvascular alterations in the mouse cerebral cortex. It alters expression of some proteins involved in epigenetic regulation of transcription, histone modification, DNA repair, nuclear protein import, and proliferation. These data indicate epigenetic markers of photo-oxidative injury of normal brain tissue. [Display omitted] •ALA-PDT kills some neurons and causes microvascular alterations in mouse brain.•PDT alters epigenetic regulation of gene transcription in mouse cerebral cortex.•PDT changes levels of proteins involved in chromatin remodeling in mouse brain.•PDT changes levels of proteins involved in DNA repair in mouse cerebral cortex.•PDT changes levels of proteins regulating cell division and survival in brain.